Wear-resistant elastic material for automobile collision dummy and preparation method thereof
By using PA in EPDM sealed products, combined with nano-scale fillers such as SWCNTs and nanographite, and using a low-sulfur and high-promotion vulcanization process, a wear-resistant elastomer material for automobile collision dummies with good wear resistance and comprehensive performance was prepared, which solved the problem of insufficient wear resistance of existing EPDM sealed products.
Patent Information
- Application Number
- CN202410957884.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-07-17
AI Technical Summary
The wear resistance of existing EPDM sealing products is weak, making it difficult to meet the higher demand for sealing material performance in the automotive industry.
EPDM and PA are used together, combined with new nano-scale fillers such as SWCNTs and nanographite, and a low-sulfur and high-promotion vulcanization process is adopted to prepare wear-resistant elastomer materials through segmented refining.
It achieves the easy preparation of materials, hardness, mechanical properties, wear resistance and rebound effects, solves the problem of insufficient wear resistance of EPDM sealed products, and maintains good comprehensive performance under high temperature aging.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of wear-resistant materials, and in particular to a wear-resistant elastic material for an automobile collision dummy and a preparation method thereof. Background Art
[0002] EPDM rubber is a highly saturated polyolefin synthetic rubber that appeared in the 1960s. It is copolymerized with three monomers: ethylene, propylene, and non-conjugated diene. The main chain of EPDM's molecular chain is completely saturated, and unsaturated double bonds exist on the side chains, which gives it good heat resistance and aging resistance, thermal stability, good insulation properties, and resistance to chemical solvents. In addition, EPDM has the characteristics of low density and high filling. In production, a large amount of fillers and oils can be added to reduce costs and improve performance. As the most widely used synthetic rubber in contemporary times, EPDM occupies an important position in the fields of construction, automotive applications, aerospace, power cables, and sporting goods.
[0003] Nylon (PA) is a new commercial crystalline plastic that has the characteristics of wear resistance, fatigue resistance, weather resistance, cold resistance, heat resistance, chemical resistance, sound absorption, processability, good thermal stability, etc. The rigid segments of PA give it good mechanical properties and wear resistance, and some flexible segments have good affinity with EPDM, which makes it possible to obtain EPDM / PA wear-resistant elastomers with excellent comprehensive performance. At present, high-performance and high-functional PA66 has strong competitiveness in industries such as the automotive industry, and has become an indispensable and important member of the nylon family.
[0004] Wear resistance refers to the ability of a material to resist mechanical wear. Under a certain load and wear rate, the wear resistance of a material is characterized by the amount of wear per unit area per unit time. At present, according to different application fields, the special rubber matrices commonly used for sealing materials are mainly: silicone rubber (Q), nitrile rubber (NBR), fluororubber (FKM), polyurethane rubber (UR) and ethylene propylene diene monomer (EPDM). EPDM has good tolerance to ozone aging, high-temperature steam, acid and alkali corrosion and natural aging, and shows excellent heat resistance stability under high temperature environment. The physical properties of nylon elastomers are less affected by temperature, and they have excellent wear resistance, durability, fatigue resistance, weather resistance and chemical resistance. They can gradually replace products such as silicone rubber and fluororubber in some fields. The new high-performance wear-resistant elastomer prepared from EPDM / PA can be used in more severe and complex working environments to meet the current market's higher demand for sealing material performance. In order to achieve the performance requirements required in practical use, the addition of fillers is particularly critical. In traditional EPDM rubber formulas, a large amount of carbon black and oil softeners are often added to meet performance requirements, but this also complicates product performance regulation. On the one hand, carbon black fillers can improve the hardness and mechanical properties of the elastomer matrix, but the system viscosity will increase significantly, making the blending and processing process very difficult, which is intuitively manifested as a large Mooney viscosity. Softeners such as paraffin oil can reduce viscosity and improve processing performance, but this will lead to a decrease in the hardness and mechanical properties of the elastomer.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a wear-resistant elastomeric material for automobile collision dummies and a preparation method thereof, so as to achieve the effects of easy preparation, good hardness, mechanical properties, wear resistance and resilience.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a wear-resistant elastomeric material for a car collision dummy, comprising the following components in parts by weight:
[0009] EPDM 100 parts, PA 5-20 parts, SWCNTs 1-10 parts, nanographite 5-20 parts, plasticizer 3-15 parts, filler 30-50 parts, activator 4-6 parts, vulcanizer 3-5 parts.
[0010] As a further preferred technical solution, the following components are included by weight:
[0011] EPDM 100 parts, PA 8-15 parts, SWCNTs 3-8 parts, nanographite 8-15 parts, plasticizer 5-10 parts, filler 35-45 parts, activator 4.5-5.5 parts, vulcanizer 3.5-4.5 parts.
[0012] As a further preferred technical solution, the Mooney viscosity of the EPDM is 50-70, and the particle size of the nanographite is 0-75 μm, excluding 0.
[0013] As a further preferred technical solution, the plasticizer is a mixture of paraffin oil and cyclohexane oil in a weight ratio of 1:2, the filler is a mixture of carbon black and white carbon black in a weight ratio of 2:1, the activator is a mixture of stearic acid and zinc oxide in a weight ratio of 1:3, and the vulcanizing agent is a mixture of sulfur, accelerator DM and accelerator CZ in a weight ratio of 5:1:2.
[0014] In a second aspect, the present invention provides a method for preparing a wear-resistant elastomeric material for a car collision dummy, comprising the following steps:
[0015] S1, melt-mixing EPDM and PA to obtain a masterbatch;
[0016] S2, mixing the masterbatch once, then adding SWCNTs, nano-graphite, plasticizer, and filler, and mixing again to obtain a rubber mixture;
[0017] S3, mixing the mixed rubber and the vulcanizing agent three times, and cutting into sheets after the three mixings are uniform, so as to obtain the desired wear-resistant elastomer material for automobile collision dummy.
[0018] As a further preferred technical solution, in S1, a twin-screw extruder is used to melt-mix EPDM and PA, the operating temperature of the twin-screw extruder is 200-220°C, and the screw speed is 190-210 rpm.
[0019] As a further preferred technical solution, in S2, an internal mixer is used for primary mixing and secondary mixing, the speed of the internal mixer is 50-70 rpm, the working temperature is 150-160°C, the time for primary mixing and secondary mixing is 5-7 minutes, and the degumming temperature is 150-170°C.
[0020] As a further preferred technical solution, in S2, before adding SWCNTs, nano-graphite and plasticizer, a first pretreatment step is also included, wherein the first pretreatment comprises: grinding and mixing SWCNTs and nano-graphite in a ball mill to obtain a SWCNTs / nano-graphite mixture, and then mixing the SWCNTs / nano-graphite mixture and the plasticizer with a blender to obtain a SWCNTs / nano-graphite / plasticizer slurry.
[0021] As a further preferred technical solution, in S2, a second pretreatment step is also included before adding the filler, and the second pretreatment includes: adding white carbon black, alcohol and silane coupling agent into a blender in a weight ratio of 10:1:0.5 and mixing them, the working temperature of the blender is 150~170℃, the stirring time is 8~12 minutes, and then the temperature is reduced to 90~110℃, and carbon black is added, and stirring is continued for 5~7 minutes to obtain a pretreated filler.
[0022] As a further preferred technical solution, in S3, an open mill is used for three mixings, the temperature of the open mill is 30-40°C, the speed is 20-30 rpm, the speed ratio is 1.2:1, and a third pretreatment step is also included before adding the vulcanizing agent. The third pretreatment includes: adding the vulcanizing agent to the natural latex in proportion, the weight ratio of the vulcanizing agent to the natural latex is 1:10, the solid content of the natural latex is 15%-25%, and the mixture is stirred and mixed evenly with a stirrer. The speed of the stirrer is 90-110 rpm, the stirring time is 9-12 minutes, and the temperature is set to 50-70°C. Finally, ethanol is added to break the emulsification, and vacuum drying is performed to obtain a pre-dispersed vulcanizing agent.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides an EPDM / PA elastomer material prepared by segmented mixing, and carbon black, SWCNTs, graphite, plasticizer and vulcanizer are combined, and each component interacts and cooperates with each other to give full play to the toughening, strengthening, wear resistance and anti-aging effects of different components. The problem of weak wear resistance of EPDM sealing products is solved, and finally a wear-resistant elastomer material suitable for automobile collision dummies with good physical and mechanical properties, wear resistance, aging resistance and weather resistance is prepared, and the material can be used for the production of automobile collision dummy skin layers.
[0025] Compared with the existing method of filling a large amount of carbon black filler and using a plasticizer, the present invention uses EPDM and PA in combination, and innovatively uses new nano-scale fillers such as SWCNTs and graphite, and adopts a low-sulfur and high-promoting vulcanization process. The high-performance wear-resistant rubber products produced require less fillers, have better processing performance, fast vulcanization speed and significantly lower density. Good comprehensive performance can still be maintained under high-temperature aging. The rigid chain segment of PA contributes to excellent wear resistance, and the affinity of the flexible segment and the EPDM molecular chain enhances the cross-linked network structure, greatly improving the reinforcement effect. SWCNTs and graphite, as nano-scale fillers, have the characteristics of low addition and high performance, which can significantly reduce the use of carbon black and oil, improve processing performance while ensuring the strength and comprehensive performance of the elastomer matrix. The stable cross-linked network structure and the three-dimensional filler network formed by the nanofillers can greatly improve the comprehensive performance of the polymer matrix material. DETAILED DESCRIPTION
[0026] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer.
[0027] In a first aspect, the present invention provides a wear-resistant elastomeric material for a car collision dummy, comprising the following components in parts by weight:
[0028] EPDM 100 parts, PA 5-20 parts, SWCNTs 1-10 parts, nanographite 5-20 parts, plasticizer 3-15 parts, filler 30-50 parts, activator 4-6 parts, vulcanizer 3-5 parts.
[0029] By weight, the amount of PA can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts. The amount of SWCNTs (single-walled carbon nanotubes) can be 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts. The amount of nanographite can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts. The amount of plasticizer can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts. The amount of filler can be 30 parts, 32 parts, 35 parts, 36 parts, 38 parts, 40 parts, 42 parts, 45 parts, 46 parts, 48 parts or 50 parts. The amount of activator can be 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts. The amount of vulcanizing agent can be 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.
[0030] The wear-resistant elastomer material for automobile collision dummies is made of EPDM, PA, carbon black, SWCNTs, graphite, plasticizer and vulcanizer. The components interact and cooperate with each other to give full play to the toughening, strengthening, wear resistance and anti-aging effects of different components. The problem of weak wear resistance of EPDM sealing products is solved, and finally a wear-resistant elastomer material for automobile collision dummies with good physical and mechanical properties, wear resistance, aging resistance and weather resistance is prepared.
[0031] Compared with the existing method of filling a large amount of carbon black filler and using a plasticizer, the present invention uses EPDM and PA in combination, and innovatively uses new nano-scale fillers such as SWCNTs and graphite, and adopts a low-sulfur and high-promoting vulcanization process. The high-performance wear-resistant rubber products produced require less fillers, have better processing performance, fast vulcanization speed and significantly lower density. Good comprehensive performance can still be maintained under high-temperature aging. The rigid chain segment of PA contributes to excellent wear resistance, and the affinity of the flexible segment and the EPDM molecular chain enhances the cross-linked network structure, greatly improving the reinforcement effect. SWCNTs and graphite, as nano-scale fillers, have the characteristics of low addition and high performance, which can significantly reduce the use of carbon black and oil, improve processing performance while ensuring the strength and comprehensive performance of the elastomer matrix. The stable cross-linked network structure and the three-dimensional filler network formed by the nanofillers can greatly improve the comprehensive performance of the polymer matrix material.
[0032] In an optional embodiment, the following components are included by weight: 100 parts of EPDM, 8-15 parts of PA, 3-8 parts of SWCNTs, 8-15 parts of nanographite, 5-10 parts of plasticizer, 35-45 parts of filler, 4.5-5.5 parts of activator, and 3.5-4.5 parts of vulcanizer. A large number of tests have found that when the content of each component is within the above range, the performance of the material is better.
[0033] In an optional embodiment, the Mooney viscosity of the EPDM is 50-70, and the particle size of the nanographite is 0-75 μm, excluding 0. The Mooney viscosity of the above EPDM can be selected from 50, 52, 55, 56, 58, 60, 62, 65, 66, 68 or 70. The particle size of the above nanographite is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm or 75 μm. Selecting a Mooney viscosity between 50 and 70 can not only ensure the excellent processing performance of EPDM, but also can well ensure the uniform dispersion of nanographite in the EPDM rubber matrix, giving EPDM good wear resistance.
[0034] In an optional embodiment, the plasticizer is a mixture of paraffin oil and naphthenic oil in a weight ratio of 1:2, the filler is a mixture of carbon black and white carbon black in a weight ratio of 2:1, the activator is a mixture of stearic acid and zinc oxide in a weight ratio of 1:3, and the vulcanizing agent is a mixture of sulfur, accelerator DM and accelerator CZ in a weight ratio of 5:1:2. Wherein, accelerator DM is dibenzothiazole disulfide, and accelerator CZ is N-cyclohexyl-2-benzothiazole sulfonamide. Paraffin oil and naphthenic oil are used together, on the one hand, to further improve the processing performance of EPDM, on the other hand, to further promote the uniform dispersion of fillers in the EPDM rubber matrix, and improve the comprehensive performance of the product. In addition, the vulcanizing agent can take into account the processing safety and mechanical properties of EPDM rubber.
[0035] In a second aspect, the present invention provides a method for preparing a wear-resistant elastomeric material for a car collision dummy, comprising the following steps:
[0036] S1, melt-mixing EPDM and PA to obtain a masterbatch;
[0037] S2, mixing the masterbatch once, then adding SWCNTs, nano-graphite, plasticizer, and filler, and mixing again to obtain a rubber mixture;
[0038] S3, mixing the mixed rubber and the vulcanizing agent three times, and cutting into sheets after the three mixings are uniform, so as to obtain the desired wear-resistant elastomer material for automobile collision dummy.
[0039] The method adopts a segmented mixing method, has reasonable process, is easy to operate, and is easy to prepare a wear-resistant elastomer material for a car collision dummy with good performance.
[0040] In an optional embodiment, in S1, a twin-screw extruder is used to melt-mix EPDM and PA, and the operating temperature of the twin-screw extruder is 200-220°C, and the screw speed is 190-210 rpm. The operating temperature of the twin-screw extruder can be selected as 200°C, 205°C, 210°C, 215°C or 220°C. The screw speed can be selected as 190 rpm, 195 rpm, 200 rpm, 205 rpm or 210 rpm. The use of a twin-screw extruder can better fuse the two materials of EPDM and PA at the molecular level and improve the compatibility between the two.
[0041] In an optional embodiment, in S2, a banbury mixer is used for primary mixing and secondary mixing, the speed of the banbury mixer is 50-70 rpm, the working temperature is 150-160°C, the time of primary mixing and secondary mixing is 5-7 minutes, and the debinding temperature is 150-170°C. The speed of the above-mentioned banbury mixer can be selected as 50 rpm, 55 rpm, 60 rpm, 65 rpm or 70 rpm. The above-mentioned working temperature can be selected as 150°C, 155°C, 160°C, 165°C or 170°C. The above-mentioned mixing time can be selected as 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes or 7 minutes. The above-mentioned debinding temperature can be selected as 150°C, 155°C, 160°C, 165°C or 170°C. The use of a banbury mixer can evenly disperse all additives and further improve the comprehensive performance of the prepared product, especially the wear resistance.
[0042] In an optional embodiment, in S2, before adding SWCNTs, nanographite, and plasticizer, a first pretreatment step is further included, wherein the first pretreatment includes: grinding and mixing SWCNTs and nanographite in a ball mill to obtain a SWCNTs / nanographite mixture, and then using a blender to mix the SWCNTs / nanographite mixture and the plasticizer to obtain a SWCNTs / nanographite / plasticizer slurry. This optional embodiment further promotes the uniform dispersion of the SWCNTs / nanographite mixture and achieves a perfect fusion of the two additives, which plays a decisive role in the wear resistance of the product of the present application.
[0043] In an optional embodiment, in S2, before adding the filler, a second pretreatment step is also included, and the second pretreatment includes: adding white carbon black, alcohol and silane coupling agent to a mixer in a weight ratio of 10:1:0.5, mixing, the working temperature of the mixer is 150~170℃, the stirring time is 8~12 minutes, then cooling to 90~110℃, adding carbon black, and continuing to stir for 5~7 minutes to obtain a pretreated filler. The working temperature of the above-mentioned mixer can be selected as 150℃, 155℃, 160℃, 165℃ or 170℃. The above-mentioned stirring time can be selected as 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes, 10 minutes, 10.5 minutes, 11 minutes, 11.5 minutes or 12 minutes. The temperature after the above-mentioned cooling can be selected as 90℃, 95℃, 100℃, 105℃ or 110℃. The above-mentioned stirring time can be selected as 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes or 7 minutes. The characteristic of white carbon black is that it is difficult to disperse. This processing step can ensure the uniform dispersion of white carbon black in the filler, and further improve the wear resistance and mechanical strength of the product of the present application.
[0044] In an optional embodiment, in S3, an open mill is used for three mixing, the temperature of the open mill is 30-40°C, the speed is 20-30 rpm, the speed ratio is 1.2:1, and a third pretreatment step is also included before adding the vulcanizing agent, the third pretreatment includes: adding the vulcanizing agent to the natural latex in proportion, the weight ratio of the vulcanizing agent to the natural latex is 1:10, the solid content of the natural latex is 15%-25%, and the stirring is uniformly mixed by a stirring bar, the speed of the stirring bar is 90-110 rpm, the stirring time is 9-12 minutes, the temperature is set to 50-70°C, and finally ethanol is added to demulsify, and vacuum drying is performed to obtain a pre-dispersed vulcanizing agent. The temperature of the above-mentioned open mill can be selected as 30°C, 35°C or 40°C. The above-mentioned speed can be selected as 20 rpm, 22 rpm, 25 rpm, 26 rpm, 28 rpm or 30 rpm. The solid content can be selected as 15%, 16%, 18%, 20%, 22%, 24% or 25%. The rotation speed of the stirring bar can be selected as 90 rpm, 95 rpm, 100 rpm, 105 rpm or 110 rpm. The stirring time can be selected as 9 minutes, 9.5 minutes, 10 minutes, 10.5 minutes, 11 minutes, 11.5 minutes or 12 minutes. The temperature can be selected as 50°C, 55°C, 60°C, 65°C or 70°C. Pre-dispersing the vulcanizing agent in advance can ensure the uniform dispersion of the vulcanizing agent in the rubber matrix. In the later product vulcanization preparation process, the uniformly dispersed vulcanizing agent can achieve perfect crosslinking of the EPDM rubber matrix, thereby further improving the comprehensive performance of the product, especially the mechanical strength.
[0045] The present invention is further described in detail below with reference to the embodiments and comparative examples.
[0046] Example 1
[0047] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0048] EPDM 100 parts, PA 20 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0049] The Mooney viscosity of EPDM is 70, and the particle size of nanographite is 75 μm.
[0050] The plasticizer is a mixture of paraffin oil and cyclohexane oil in a weight ratio of 1:2, the filler is a mixture of carbon black and white carbon black in a weight ratio of 2:1, the activator is a mixture of stearic acid and zinc oxide in a weight ratio of 1:3, and the vulcanizer is a mixture of sulfur, accelerator DM and accelerator CZ in a weight ratio of 5:1:2.
[0051] The wear-resistant elastomer material for the automobile collision dummy is prepared by the following method:
[0052] S1, melt-mixing EPDM and PA to obtain a masterbatch;
[0053] S2, mixing the masterbatch once, then adding SWCNTs, nano-graphite, plasticizer, and filler, and mixing again to obtain a rubber mixture;
[0054] S3, mixing the mixed rubber and the vulcanizing agent three times, and cutting into sheets after the three mixings are uniform, so as to obtain the desired wear-resistant elastomer material for automobile collision dummy.
[0055] In S1, a twin-screw extruder is used to melt-mix EPDM and PA. The operating temperature of the twin-screw extruder is 200° C. and the screw speed is 200 rpm.
[0056] In S2, an internal mixer is used for primary mixing and secondary mixing. The speed of the internal mixer is 60 rpm, the working temperature is 160°C, the time for primary mixing and secondary mixing is 5 minutes, and the debonding temperature is 160°C.
[0057] In S2, before adding SWCNTs, nanographite and plasticizer, a first pretreatment step is also included, wherein the first pretreatment comprises: grinding and mixing SWCNTs and nanographite in a ball mill to obtain a SWCNTs / nanographite mixture, and then mixing the SWCNTs / nanographite mixture and the plasticizer with a blender to obtain a SWCNTs / nanographite / plasticizer slurry.
[0058] In S2, a second pretreatment step is also included before adding the filler, and the second pretreatment includes: adding white carbon black, alcohol and silane coupling agent in a weight ratio of 10:1:0.5 into a mixer and mixing them, the working temperature of the mixer is 160°C, the stirring time is 10 minutes, and then the temperature is lowered to 100°C, and carbon black is added, and stirring is continued for 5 minutes to obtain a pretreated filler.
[0059] In S3, an open mill is used for three mixing, the temperature of the open mill is 30°C, the speed is 30 rpm, and the speed ratio is 1.2:1. Before adding the vulcanizing agent, a third pretreatment step is also included, and the third pretreatment includes: adding the vulcanizing agent to the natural latex in proportion, the weight ratio of the vulcanizing agent to the natural latex is 1:10, the solid content of the natural latex is 20%, and the mixing is uniformly stirred with a stirrer, the speed of the stirrer is 100 rpm, the stirring time is 10 minutes, and the temperature is set to 60°C. Finally, ethanol is added to break the emulsification, and vacuum drying is performed to obtain a pre-dispersed vulcanizing agent.
[0060] Example 2
[0061] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0062] EPDM 100 parts, PA 20 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0063] The difference between this embodiment and embodiment 1 is that the plasticizer is paraffin oil, and the other components and contents are the same as those in embodiment 1.
[0064] Example 3
[0065] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0066] EPDM 100 parts, PA 20 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0067] The difference between this embodiment and embodiment 1 is that the filler is white carbon black, and the other components and contents are the same as those in embodiment 1.
[0068] Example 4
[0069] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0070] EPDM 100 parts, PA 20 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0071] The difference between this embodiment and embodiment 1 is that the activator is zinc oxide, and the other components and contents are the same as those in embodiment 1.
[0072] Example 5
[0073] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0074] EPDM 100 parts, PA 20 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0075] The difference between this embodiment and embodiment 1 is that the vulcanizing agent is accelerator DM, and the other components and contents are the same as those in embodiment 1.
[0076] Example 6
[0077] A wear-resistant elastomeric material for a car collision dummy, the components and contents of which are the same as those in Example 1, except for the preparation method, which comprises the following steps:
[0078] S1, melt-mixing EPDM and PA to obtain a masterbatch;
[0079] S2, mixing the masterbatch once, then adding SWCNTs, nano-graphite, plasticizer, and filler, and mixing again to obtain a rubber mixture;
[0080] S3, mixing the mixed rubber and the vulcanizing agent three times, and cutting into sheets after the three mixings are uniform, so as to obtain the desired wear-resistant elastomer material for automobile collision dummy.
[0081] In S1, a twin-screw extruder is used to melt-mix EPDM and PA. The operating temperature of the twin-screw extruder is 220° C. and the screw speed is 190 rpm.
[0082] In S2, an internal mixer is used for primary mixing and secondary mixing. The speed of the internal mixer is 50 rpm, the working temperature is 150°C, the time for primary mixing and secondary mixing is 7 minutes, and the debonding temperature is 150°C.
[0083] In S2, before adding SWCNTs, nanographite and plasticizer, a first pretreatment step is also included, wherein the first pretreatment comprises: grinding and mixing SWCNTs and nanographite in a ball mill to obtain a SWCNTs / nanographite mixture, and then mixing the SWCNTs / nanographite mixture and the plasticizer with a blender to obtain a SWCNTs / nanographite / plasticizer slurry.
[0084] In S2, a second pretreatment step is also included before adding the filler, and the second pretreatment includes: adding white carbon black, alcohol and silane coupling agent into a mixer in a weight ratio of 10:1:0.5 and mixing them. The working temperature of the mixer is 150°C, the stirring time is 12 minutes, and then the temperature is lowered to 90°C, and carbon black is added, and stirring is continued for 7 minutes to obtain a pretreated filler.
[0085] In S3, an open mill is used for three mixing, the temperature of the open mill is 40°C, the speed is 20 rpm, and the speed ratio is 1.2:1. Before adding the vulcanizing agent, a third pretreatment step is also included, and the third pretreatment includes: adding the vulcanizing agent to the natural latex in proportion, the weight ratio of the vulcanizing agent to the natural latex is 1:10, the solid content of the natural latex is 15%, and the mixing is uniformly stirred with a stirrer, the speed of the stirrer is 90 rpm, the stirring time is 12 minutes, and the temperature is set to 50°C. Finally, ethanol is added to break the emulsification, and vacuum drying is performed to obtain a pre-dispersed vulcanizing agent.
[0086] Example 7
[0087] A wear-resistant elastomeric material for a car collision dummy, the components and contents of which are the same as those in Example 1, except for the preparation method, which comprises the following steps:
[0088] S1, melt-mixing EPDM and PA to obtain a masterbatch;
[0089] S2, mixing the masterbatch once, then adding SWCNTs, nano-graphite, plasticizer, and filler, and mixing again to obtain a rubber mixture;
[0090] S3, mixing the mixed rubber and the vulcanizing agent three times, and cutting into sheets after the three mixings are uniform, so as to obtain the desired wear-resistant elastomer material for automobile collision dummy.
[0091] In S1, a twin-screw extruder is used to melt-mix EPDM and PA. The operating temperature of the twin-screw extruder is 210° C. and the screw speed is 190 rpm.
[0092] In S2, an internal mixer is used for primary mixing and secondary mixing. The speed of the internal mixer is 70 rpm, the working temperature is 155°C, the time for primary mixing and secondary mixing is 6 minutes, and the debonding temperature is 155°C.
[0093] In S2, before adding SWCNTs, nanographite and plasticizer, a first pretreatment step is also included, wherein the first pretreatment comprises: grinding and mixing SWCNTs and nanographite in a ball mill to obtain a SWCNTs / nanographite mixture, and then mixing the SWCNTs / nanographite mixture and the plasticizer with a blender to obtain a SWCNTs / nanographite / plasticizer slurry.
[0094] In S2, a second pretreatment step is also included before adding the filler, and the second pretreatment includes: adding white carbon black, alcohol and silane coupling agent into a mixer in a weight ratio of 10:1:0.5 and mixing them. The working temperature of the mixer is 170°C, the stirring time is 8 minutes, and then the temperature is lowered to 110°C, and carbon black is added, and stirring is continued for 6 minutes to obtain a pretreated filler.
[0095] In S3, an open mill is used for three mixing, the temperature of the open mill is 40°C, the speed is 20 rpm, and the speed ratio is 1.2:1. Before adding the vulcanizing agent, a third pretreatment step is also included, and the third pretreatment includes: adding the vulcanizing agent to the natural latex in proportion, the weight ratio of the vulcanizing agent to the natural latex is 1:10, the solid content of the natural latex is 20%, and the mixing is uniformly stirred with a stirrer, the speed of the stirrer is 110 rpm, the stirring time is 9 minutes, and the temperature is set to 70°C. Finally, ethanol is added to break the emulsification, and vacuum drying is performed to obtain a pre-dispersed vulcanizing agent.
[0096] Example 8
[0097] A wear-resistant elastomeric material for a car collision dummy, the components and contents of which are the same as those in Example 1, except for the preparation method, which comprises the following steps:
[0098] All the materials were put into an internal mixer for mixing. The speed of the internal mixer was 70 rpm, the working temperature was 160° C., and the mixing time was 20 minutes to obtain the desired wear-resistant elastomer material for automobile collision dummies.
[0099] Example 9
[0100] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0101] EPDM 100 parts, PA 5 parts, SWCNTs 10 parts, nanographite 20 parts, plasticizer 3 parts, filler 30 parts, activator 4 parts, vulcanizer 3 parts.
[0102] The preparation method is the same as that in Example 1.
[0103] Example 10
[0104] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0105] EPDM 100 parts, PA 15 parts, SWCNTs 5 parts, nanographite 15 parts, plasticizer 10 parts, filler 40 parts, activator 5 parts, vulcanizer 4 parts.
[0106] The preparation method is the same as that in Example 1.
[0107] Comparative Example 1
[0108] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0109] EPDM 100 parts, nano graphite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0110] The difference between this comparative example and Example 1 is that the components do not contain PA and SWCNTs, and the other components and preparation methods are the same as those in Example 1.
[0111] Comparative Example 2
[0112] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0113] EPDM 100 parts, PA 20 parts, multi-walled carbon nanotubes 1 part, nano-graphite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0114] The difference between this comparative example and Example 1 is that the SWCNTs in the components are replaced by multi-walled carbon nanotubes, and the other components and preparation methods are the same as those in Example 1.
[0115] Comparative Example 3
[0116] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0117] EPDM 100 parts, SWCNTs 1 part, nanographite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0118] The difference between this comparative example and Example 1 is that PA is not included in the components, and the remaining components and preparation method are the same as those in Example 1.
[0119] Comparative Example 4
[0120] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0121] EPDM 100 parts, PA 20 parts, nano graphite 5 parts, plasticizer 15 parts, filler 50 parts, activator 6 parts, vulcanizer 5 parts.
[0122] The difference between this comparative example and Example 1 is that the components do not contain SWCNTs, and the other components and preparation methods are the same as those in Example 1.
[0123] Comparative Example 5
[0124] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0125] 100 parts of EPDM, 20 parts of nanographite, 3 parts of plasticizer, 30 parts of filler, 4 parts of activator, and 3 parts of vulcanizer.
[0126] The difference between this comparative example and Example 9 is that the components do not contain PA and SWCNTs, and the other components and preparation methods are the same as those of Example 9.
[0127] Comparative Example 6
[0128] A wear-resistant elastomer material for a car collision dummy, comprising the following components in parts by weight:
[0129] EPDM 100 parts, nano graphite 15 parts, plasticizer 10 parts, filler 40 parts, activator 5 parts, vulcanizer 4 parts.
[0130] The difference between this comparative example and Example 10 is that the components do not contain PA and SWCNTs, and the other components and preparation methods are the same as those of Example 10.
[0131] The wear-resistant elastomers in the above embodiments and comparative examples were vulcanized to prepare rubber products. The performance test results of the prepared rubber products are shown in Table 1, and the thermal oxidation aging performance (150° C., 48 hours) is shown in Table 2.
[0132] Table 1
[0133]
[0134] Table 2
[0135]
[0136] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.
Claims
1. A wear-resistant elastomeric material for a car collision dummy, characterized in that: By weight, it contains the following components: EPDM 100 parts, PA 5-20 parts, SWCNTs 1-10 parts, nanographite 5-20 parts, plasticizer 3-15 parts, filler 30-50 parts, activator 4-6 parts, vulcanizer 3-5 parts; The plasticizer is a mixture of paraffin oil and cyclohexane oil in a weight ratio of 1:2, the filler is a mixture of carbon black and white carbon black in a weight ratio of 2:1, the activator is a mixture of stearic acid and zinc oxide in a weight ratio of 1:3, and the vulcanizer is a mixture of sulfur, accelerator DM and accelerator CZ in a weight ratio of 5:1:
2.
2. The wear-resistant elastic material for automobile collision dummy according to claim 1, characterized in that: By weight, it contains the following components: EPDM 100 parts, PA 8-15 parts, SWCNTs 3-8 parts, nanographite 8-15 parts, plasticizer 5-10 parts, filler 35-45 parts, activator 4.5-5.5 parts, vulcanizer 3.5-4.5 parts.
3. The wear-resistant elastic material for automobile collision dummy according to claim 1, characterized in that: The Mooney viscosity of the EPDM is 50-70, and the particle size of the nanographite is 0-75 μm, excluding 0.
Citation Information
Patent Citations
High-strength oil-resistant ethylene propylene rubber cable material
CN103571067A
Low-Mooney high-hardness ethylene propylene diene monomer composite material and preparation method thereof
CN115612214A